2020
DOI: 10.1101/2020.05.05.20092023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental Health Impact of COVID-19: A global study of risk and resilience factors

Abstract: This study anonymously screened 13,332 individuals worldwide for psychological symptoms related to Corona virus disease 2019 (COVID-19) pandemic from March 29 th to April 14 th , 2020. A total of n=12,817 responses were considered valid with responses from 12 featured countries and five WHO regions. Female gender, pre-existing psychiatric condition, and prior exposure to trauma were identified as notable risk factors, whereas optimism, ability to share concerns with family and friends like usual, positive pred… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 49 publications
7
89
0
3
Order By: Relevance
“…Additionally, this research suggests, in line with other studies, that maintaining work, exercising, having a garden at home, and spending less time consuming COVID-19-related information in the media are protective factors against psychological symptoms (12). Optimism and social support were also found to be important resilience factors (10).…”
Section: On the General Populationsupporting
confidence: 86%
See 2 more Smart Citations
“…Additionally, this research suggests, in line with other studies, that maintaining work, exercising, having a garden at home, and spending less time consuming COVID-19-related information in the media are protective factors against psychological symptoms (12). Optimism and social support were also found to be important resilience factors (10).…”
Section: On the General Populationsupporting
confidence: 86%
“…As previously mentioned, research showed that regular physical activity is associated with better psychological outcomes during the COVID-19 outbreak (10,12). Simple exercises can be performed at home during daily tasks (e.g., walking in the house and to the grocery store, lifting groceries, climbing stairs), with the guidance of internet videos, TV, or mobile apps (e.g., yoga, Pilates, toning workout) or even without external tools (e.g., sit-ups, push-ups, squats) (53).…”
Section: Self-care Practicesmentioning
confidence: 78%
See 1 more Smart Citation
“…Four studies had a prospective longitudinal design [26,29,39,36], one was a cross-sectional study with a retrospective measure of the exposure factor (henceforth treated as retrospective) [5], and 16 were crosssectional studies [9, 23-25, 27, 29-35, 37, 6, 38, 40, 28, 41]. A total of 7 studies were conducted in Asia [24,25,27,30,33,39,40], 6 in Europe [9,26,31,32,35,36], 3 in South America [28,29,6], 3 in North America [23,34,5], one in Oceania [38] and one study included a multinational sample [37].…”
Section: Resultsmentioning
confidence: 99%
“…Results are summarized and presented in table 2. Out of 9 studies reporting analyses on the association between the overall volume of PA and depression, 6 studies showed that more PA is signi cantly associated with less depression symptoms [23,25,32,33,35,37], and 3 out of 8 studies investigating the association between the overall volume of PA and anxiety symptoms showed that more PA is signi cantly associated with less anxiety symptoms [25,32,35]. 3 out of 5 studies reported higher frequencies of PA to be signi cantly associated with less depression [27,29,36] and 2 out of 4 studies to be signi cantly associated with less anxiety [27,29].…”
Section: Resultsmentioning
confidence: 99%